Housing, crises and crime - Braithwaite, John (Journal of criminology, 2021)
A disappointment of responses to the Covid-19 crisis is that governments have not invested massively in public housing. Global crises are opportunities for macro resets of policy settings that might deliver lower crime and better justice. Justice Reinvestment is important, but far from enough, as investment beyond the levels of capital sunk into criminal justice is required to establish a just society. Neoliberal policies have produced steep declines in public and social housing stock. This matters because many rehabilitation programmes only work when clients have secure housing. Getting housing policies right is also fundamental because we know the combined effect on crime of being truly disadvantaged, and living in a deeply disadvantaged neighbourhood, is not additive, but multiplicative. A Treaty with First Nations Australians is unlikely to return the stolen land on which white mansions stand. Are there other options for Treaty negotiations? Excellence and generosity in social housing policies might open some paths to partial healing for genocide and ecocide.